1998
DOI: 10.1152/ajpgi.1998.275.1.g95
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between neurokinin A, VIP, prostanoids, and enteric nerves in regulation of duodenal function

Abstract: Neurokinin A (NKA) induces duodenal motility and increases mucosal permeability and bicarbonate secretion in the in situ perfused duodenum in anesthetized rats. In the present study, the NKA-induced increase in mucosal permeability was potentiated by luminal perfusion with lidocaine and diminished by vasoactive intestinal peptide (VIP) but unaltered by elevated intraluminal pressure. Elevation of intraluminal pressure, however, potentiated the stimulatory effect of NKA on bicarbonate secretion. In contrast, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Although the majority of VIP is probably of neuronal origin, one cannot exclude the finding that VIP can also be released by other cells such as lymphocytes (21). Our results obtained after activation of human submucosal neurons are reinforced by an in vivo study showing that VIP was able to reduce the increase in paracellular permeability induced by substance P in the rat (14). VIP has also been reported to decrease transepithelial resistance in Caco-2 and HT29-Cl.19A cell lines (5).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Although the majority of VIP is probably of neuronal origin, one cannot exclude the finding that VIP can also be released by other cells such as lymphocytes (21). Our results obtained after activation of human submucosal neurons are reinforced by an in vivo study showing that VIP was able to reduce the increase in paracellular permeability induced by substance P in the rat (14). VIP has also been reported to decrease transepithelial resistance in Caco-2 and HT29-Cl.19A cell lines (5).…”
Section: Discussionmentioning
confidence: 54%
“…Both in vivo or in vitro approaches have been employed in the few studies that have explored interactions between enteric neurons and the intestinal epithelial barrier. In vivo studies in animal models have suggested that neuromediators such as VIP, substance P, or acetylcholine are involved in the regulation of intestinal permeability (14,15,17). Although closely reproducing physiological conditions, these studies make difficult the accurate analysis of the regulatory mechanisms at cellular or molecular levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In several tissues, including rat duodenum, there is evidence for tachykinin-prostaglandin interactions (Hallgren et al, 1998), but this did not seem to be the case in human sigmoid colon circular muscle. We found that a minor component of the contractile response was apparently due to Ach release, as in guinea pig ileum (Holzer and Lembeck, 1980), because responses to SP (but not to NKA) were slightly but significantly inhibited by atropine.…”
Section: Substance P In the Human Colon 633mentioning
confidence: 91%
“…In pigs, tetrodotoxin (TTX, a blocker of Na + channels) increased basal jejunal paracellular permeability suggesting that a basal neuronal activity exerts an inhibitory tonus on intestinal permeability (Hayden & Carey, 2000). In vivo studies in animal models suggested that different neuromediators participate in this regulation (Hällgren et al . 1998; Hayden & Carey, 2000).…”
Section: Introductionmentioning
confidence: 99%